1998
DOI: 10.1017/s1357729800009814
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of potentially toxic elements by sheep given diets containing soil and sewage sludge. 1. Effect of type of soil and level of sewage sludge in the diet

Abstract: Increasing amounts of sewage sludge will be applied to agricultural land over the next 10 years as a result of the prohibition of its disposal to the sea. The addition of potentially toxic elements (PTEs) to the soil via sewage sludge is controlled by European legislation designed to limit the accumulation of PTEs in soil which could give rise to toxicity to plants or livestock. However the possibility exists that direct ingestion of sewage sludge and soil together with grazed herbage may result in accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
3
16
1
Order By: Relevance
“…Despite the fact that Cu concentrations were slightly higher in T than C plots, concentrations were lower in T than C lamb tissues. This is also consistent with previous reports (Hill et al, 1998a and b) but in the present study this difference was shown to occur in ewe tissues as well as in lambs, although concentrations were generally higher in the latter. This apparent anomaly in the patterns of soil and tissue concentrations with respect to Cu, is probably a reflection of the many factors that affect assimilation in animal tissues.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Despite the fact that Cu concentrations were slightly higher in T than C plots, concentrations were lower in T than C lamb tissues. This is also consistent with previous reports (Hill et al, 1998a and b) but in the present study this difference was shown to occur in ewe tissues as well as in lambs, although concentrations were generally higher in the latter. This apparent anomaly in the patterns of soil and tissue concentrations with respect to Cu, is probably a reflection of the many factors that affect assimilation in animal tissues.…”
Section: Discussionsupporting
confidence: 94%
“…While exposure to sludge had no significant effects on any of the tissue concentrations of Cd, Cr, Hg or Ni, as reported previously (Hill et al, 1998a and b), the results indicated that the patterns of accumulation of other metals differed with age and/or stage of development. Despite the fact that Cu concentrations were slightly higher in T than C plots, concentrations were lower in T than C lamb tissues.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…An investigation of the accumulation of potentially toxic elements (PTEs) by sheep given diets containing different levels of sewage sludge (Hill et al, 1998) found significant increases in the concentrations of Cd and Pb in liver and kidney but not in muscle tissue. The rate of accumulation of PTEs, especially Cd and Pb, declined with increasing animal age and as the level of PTEs in the diet was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…When evaluating livestock exposure to HMs it is important to consider that dietary exposure will be highly conditioned by husbandry practices, dietary ingredients, soil ingestion or spurious soil contamination in foliage being responsible for the main HM exposure [7][8][9].The HM contamination soils has become serious environmental issue around the world for various reasons, including industrial activities, solid waste disposal, fertilizers, pesticides, sludge application, irrigation with wastewater, and automobile exhausts [10][11][12][13].Beside, anthropogenic and geologic materials, soil character, mobility of the elements, weathering processes and environmental factors have remarkable effects on distribution [14,15]. It is important to have in mind how management practices can contribute to enhancing livestock metal exposures in order to minimize their toxic effect on animals, as well as to limit metal transfer to human feeds as much as possible.…”
Section: Introductionmentioning
confidence: 99%